KEPATUHAN WAJIB PAJAK ORANG PRIBADI YANG DIPENGARUHI OLEH SANKSI PAJAK, MOTIVASI DAN TINGKAT PENDIDIKAN - Cut Martlita Ariestiani; Putri Arini Septya Agustin; Pramandyah Fitah Kusuma (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
This reasearch aims to examine and analyze the effect of tax sanctions, motivation and level of education on taxpayer compliance behavior in the Pakal district of Surabaya. The unit of analysis in this study is an individual taxpayer who is domiciled in the Pakal district as many as 100 people. The sampling technique used purposive sampling. Data analysis used multiple linear regression method. The results of the study show that tax sanctions have a significant effect on taxpayer compliance. Taxpayer motivation has a significant effect on taxpayer compliance. Education level has a significant effect on taxpayer compliance. Thus, it is concluded that tax sanctions, taxpayer motivation and education level have a significant effect on individual taxpayer compliance who live in the Pakal district of Surabaya.